1993
DOI: 10.1017/s1446788700036983
|View full text |Cite
|
Sign up to set email alerts
|

Biduals of weighted banach spaces of analytic functions

Abstract: For a positive continuous weight function v on an open subset G of C , let Hv(G) and HVQ(G) denote the Banach spaces (under the weighted supremum norm) of all holomorphic functions / on G such that vf is bounded and vf vanishes at infinity, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 12 publications
1
111
0
Order By: Relevance
“…Hence, from the τ co -compactness of the closed unit ball and the τ co -continuity of T, [4] and [6]. It is a well-known fact that…”
Section: Proof the Equivalences (I)-(ii) And (Iii)-(iv) Follow From mentioning
confidence: 96%
“…Hence, from the τ co -compactness of the closed unit ball and the τ co -continuity of T, [4] and [6]. It is a well-known fact that…”
Section: Proof the Equivalences (I)-(ii) And (Iii)-(iv) Follow From mentioning
confidence: 96%
“…This is also true if we deal with G = C and we consider any radial weight which is rapidly decreasing at infinity (i.e., H v (C) contains the polynomials). These results can be found in [5] and some extensions dealing with domains G ⊂ C n , n > 1, can be found in [2]. Boyd and Rueda have studied this problem recently connecting it with the study of M-ideals in weighted spaces of holomorphic functions (see [13]).…”
Section: There Are Many Examples Of Weights V and Open Setsmentioning
confidence: 99%
“…These spaces are Banach spaces endowed with the norm · v and they appear in the study of growth conditions of analytic functions. We refer to [1], [3], [4], [5], [16], [17], [23], [25], and others for further information about these spaces. The study of composition operators on these spaces can be found in [7], [8] and [10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we also have Hv ∼ l ∞ . (Alternatively, we could have used Proposition 5.2 or [1,18] to see that hv ∼ (hv) * * 0 ∼ l ∞ and Hv ∼ (Hv) * * 0 ∼ l ∞ . )…”
Section: Conditions (B) and ¬(B)mentioning
confidence: 99%